KAJIAN USULAN ZONA KHUSUS TAMAN NASIONAL KUTAI - Reny Sawitri; Yelin Adalina (Pusat Penelitian dan Pengembangan Hutan, 2016)
ABSTRACTThe construction of the arterial road of Bontang-Sangatta in Kutai National Park triggering tenurial and wildlife conflicts due to communities occupation. Therefore, it should be managed into a special use zone. The objective of the study was to evaluate special use zone proposal, associated with the typology of ethnic communities, biophysical potency, as well as the communities perception. Structured questionnaires were used to interview 58 households. The proposed special use zone should urgently be defined considering of increasing communities population density of about 22% per year, and land encroachment of about ≥ 2 ha in Teluk Pandan and South Sangatta Sub-District. Land management lead to decreasing soil fertility. Rubber estate, however, enlarged orangutan home range. Communities perception revealed that 45% of the community wish that the area status is an enclave. It was indicated that most of the people wanted to stay in the area. The study identified 18.831 ha as a suitable area for a special use zone. The proposed zone should be arranged into three zones i.e., cultivation zone (250 m), interaction zone (251-750 m) and green belt zone (>751 m) from either side of the arterial Bontang-Sangatta road. The farmer and fishermen communities should also be advocated.Key words : Kutai National Park, special use zone, perception and managementABSTRAKPembangunan jalan poros Bontang-Sangatta di Taman Nasional Kutai memicu terjadinya konflik tenurial maupun konflik satwa, karena okupasi masyarakat. Kondisi ini mengarahkan pengelolaan kawasan ini menjadi zona khusus, untuk itu tujuan penelitian ini mengevaluasi usulan zona khusus dihubungkan dengan tipologi etnis masyarakat, potensi biofisik kawasan dan persepsi masyarakat. Metode penelitian dilakukan melalui wawancara dan kuesioner pada 58 Kepala Keluarga (KK). Usulan zona khusus ini layak ditetapkan mengingat peningkatan kepadatan penduduk sekitar 22% per tahun dan peningkatan pengusahaan lahan ≥ 2 ha pada masyarakatdi Kecamatan Teluk Pandan dan Sangatta Selatan. Pengelolaan dan pemanfaatan lahan berdampak pada menurunnya kesuburan lahan. Sementara itu, keberadaan perkebunan karet memperluas daerah jelajah satwa terutama orangutan. Persepsi masyarakat terhadap status kawasan yang menghendaki enclave (45%) mengindikasikan bahwa mereka masih menginginkan menetapdi kawasan. Usulan hasil penelitian ini, pengelolaan kawasan seluas 18.831ha layak sebagai zona khusus dan penataan lahannya terbagi ke dalam zona budidaya selebar 250 m di kiri kanan jalan Bontang-Sangatta, zona interaksi selebar 251-750 m serta kawasan hijau yang berfungsi sebagai koridor > 751 m disertai pembinaan kelompok tani dan nelayan masyarakat.Kata kunci : Persepsi dan pengelolaan, Taman Nasional Kutai, zona khusus